1997
DOI: 10.1002/ana.410420505
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term stroke risk in children with sickle cell disease screened with transcranial doppler

Abstract: Stroke is an important complication of sickle cell disease. Stroke prediction is clinically important because it offers the possibility of primary prevention. In 1992, transcranial Doppler (TCD) evidence of elevated intracranial internal carotid or middle cerebral artery velocity was demonstrated to be associated strongly with an increased risk of ischemic stroke. This study extends the original study and includes 125 more children, longer follow-up, and intracranial hemorrhage in the stroke-risk model. Elevat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
299
1
5

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 366 publications
(320 citation statements)
references
References 17 publications
7
299
1
5
Order By: Relevance
“…The cost-effectiveness, portability and repeatability of TCD make it an ideal neuroimaging technique, especially for patients with SCD who need regular monitoring for primary stroke prevention 2,5,6 . Patients with SCD are at risk for a spectrum of brain injuries such as subclinical infarction, acute ischemic stroke and hemorrhage due to the high level of circulating irreversibly-sickled red blood cells and their adherence to the vascular endothelium.…”
Section: Discussionmentioning
confidence: 99%
“…The cost-effectiveness, portability and repeatability of TCD make it an ideal neuroimaging technique, especially for patients with SCD who need regular monitoring for primary stroke prevention 2,5,6 . Patients with SCD are at risk for a spectrum of brain injuries such as subclinical infarction, acute ischemic stroke and hemorrhage due to the high level of circulating irreversibly-sickled red blood cells and their adherence to the vascular endothelium.…”
Section: Discussionmentioning
confidence: 99%
“…One hundred ninety children were screened with TCD and followed for an average of 29 months; 23 had a TAMX >170 cm/s; strokes occurred in seven patients, including six among the 23 patients with abnormal TCD. This result was confirmed by a subsequent study [23] including 125 more children, which showed that a TAMX ≥200 cm/s in the terminal ICA, or in the MCA, indicates a 10% risk for stroke per year, compared to a 2% risk in patients with normal TCD.…”
Section: Indicationsmentioning
confidence: 57%
“…In STOP-I [18], the diagnostic distribution at initial TCD examinations was: 67% normal, 17.6% conditional, 9.3% abnormal, and 6% inadequate. In a French cohort [14], TCD was abnormal in 21% of SCA-patients at a median age of 3.2 years (range, 1.3-8.3).…”
Section: Indicationsmentioning
confidence: 94%
See 2 more Smart Citations